Phase characteristics of E class amplifier with various output networks - Крижановський, В.Г. (Radiotekhnika, 2020)
Phase shift of E class amplifiers with classical output network and output network that satisfies E class loading impedance conditions twice in the frequency band were studied by simulation and experimentally. The phase shift across switch in nominal operation mode was investigated analytically. The phase shift across switch in suboptimal class E operation mode that occurs while altering the operation frequency was investigated as well. The simulation method was the harmonic balance analysis using the switch model that considers the structure of power MOSFET device, namely, the existence of antiparallel diode pair that alters the switch current waveform. The input and transition capacitances of the transistor were considered. Experimental measurement of the phase shift was performed utilizing the recorded digitized waveforms of the switch input and output voltages by computing the phases of the voltages’ first harmonics with the help of Fast Fourier Transform. It was observed that characteristics of phase shift at switch output and amplifier output are dependent on the kind of load network. The relationship between the phase shift at the switch and hodograph of the loading impedance was demonstrated. For the network with double fulfilment of class E conditions that has a loop in the loading impedance hodograph the switch phase shift dependency has an extremum, which provides an opportunity to obtain the same phase shift at two frequencies within the operating frequency band. That facilitates control of the phase-frequency characteristic and the group delay of the amplifier. Knowledge of the phase-frequency dependency simplifies the conditions for calculation of the phase shift in the feedback network. The obtained results are useful for design of class E oscillator operating in a wide frequency band.